Right Ventricle Has Normal Myofilament Function But Shows Perturbations in the Expression of Extracellular Matrix Genes in Patients With Tetralogy of Fallot Undergoing Pulmonary Valve Replacement. Issue 16 (18th August 2020) - Brayson, Daniel; Holohan, So‐Jin; Bardswell, Sonya C.; Arno, Matthew; Lu, Han; Jensen, Hanna K.; Tran, Phan Kiet; Barallobre‐Barreiro, Javier; Mayr, Manuel; dos Remedios, Cristobal G.; Tsang, Victor T.; Frigiola, Alessandra; et al.
Abstract : Background: Patients with repair of tetralogy of Fallot (rToF) who are approaching adulthood often exhibit pulmonary valve regurgitation, leading to right ventricle (RV) dilatation and dysfunction. The regurgitation can be corrected by pulmonary valve replacement (PVR), but the optimal surgical timing remains under debate, mainly because of the poorly understood nature of RV remodeling in patients with rToF. The goal of this study was to probe for pathologic molecular, cellular, and tissue changes in the myocardium of patients with rToF at the time of PVR. Methods and Results: We measured contractile function of permeabilized myocytes, collagen content of tissue samples, and the expression of mRNA and selected proteins in RV tissue samples from patients with rToF undergoing PVR for severe pulmonary valve regurgitation. The data were compared with nondiseased RV tissue from unused donor hearts. Contractile performance and passive stiffness of the myofilaments in permeabilized myocytes were similar in rToF‐PVR and RV donor samples, as was collagen content and cross‐linking. The patients with rToF undergoing PVR had enhanced mRNA expression of genes associated with connective tissue diseases and tissue remodeling, including the small leucine‐rich proteoglycans ASPN (asporin), LUM (lumican), and OGN (osteoglycin), although their protein levels were not significantly increased. Conclusions: RV myofilaments from patients with rToF undergoing PVR showed no functional impairment, but the changes in extracellular matrix gene expression may indicate the early stages of remodeling. Our study found no evidence of major damage at the cellular and tissue levels in the RV of patients with rToF who underwent PVR according to current clinical criteria.